2007
DOI: 10.1088/0264-9381/24/11/003
|View full text |Cite
|
Sign up to set email alerts
|

Plebanski theory and covariant canonical formulation

Abstract: We establish an equivalence between the Hamiltonian formulation of the Plebanski action for general relativity and the covariant canonical formulation of the HilbertPalatini action. This is done by comparing the symplectic structures of the two theories through the computation of Dirac brackets. We also construct a shifted connection with simplified Dirac brackets, playing an important role in the covariant loop quantization program, in the Plebanski framework. Implications for spin foam models are also discus… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(64 citation statements)
references
References 27 publications
1
63
0
Order By: Relevance
“…If such a relation exists, it should rely on a more sophisticated choice of reality conditions. Finally, we have also observed that there are sectors in phase space, characterized by vanishing of the two (partial Dirac) brackets (52), where this classification of constraints may fail, in particular, leading to fewer degrees of freedom. In fact, the existence of special sectors in phase space with a drastically different canonical structure is not an unusual situation.…”
Section: Discussionmentioning
confidence: 66%
“…If such a relation exists, it should rely on a more sophisticated choice of reality conditions. Finally, we have also observed that there are sectors in phase space, characterized by vanishing of the two (partial Dirac) brackets (52), where this classification of constraints may fail, in particular, leading to fewer degrees of freedom. In fact, the existence of special sectors in phase space with a drastically different canonical structure is not an unusual situation.…”
Section: Discussionmentioning
confidence: 66%
“…In fact this choice is physically motivated as SU (2) is the gauge group if we want to include fermionic matter [272]. 14 In the physics of the standard model we are used to identifying the coordinate t with the physical time of a suitable family of observers. In the general covariant context of gravitational physics the coordinate time t plays the role of a label with no physical relevance.…”
Section: Canonical Analysismentioning
confidence: 99%
“…Alternatively, one can associate the boundary states with elements of L 2 (Spin(4) N ℓ ) (in the Riemannian models) -or carefully define the analog of spin network states as distributions in the Lorentzian case 25 . In this case one gets special kind of spin network states that are a subclass of the so-called projected spin networks introduced in [16,241] in order to define an heuristic quantization of the (non-commutative and very complicated) Dirac algebra of a Lorentz connection formulation of the phase space of gravity [14,10,16,9,8,7,15]. The fact that these special subclass of projected spin networks appear naturally as boundary states of the new spin foams is shown in [152].…”
Section: Boundary Data For the New Models And Relationship With The Cmentioning
confidence: 99%
“…We will proceed in two steps, motivated by the structure of (15). First, we focus on a single link, studying the phase space T * SL(2, C) and the pair of simplicity constraints (14), which are local on the links.…”
Section: Simple Bivectors and Null Polyhedramentioning
confidence: 99%
“…Hence, the node algebra contains 2m − 1 first class constraints and two pairs of second class constraints. Using this result, and reintroducing the F 1 's (one independent first class constraint per link), the counting of dimensions of the reduced phase space S Γ defined in (15) gives…”
Section: Null Twisted Geometriesmentioning
confidence: 99%